Increased sustainability in Aquaculture – with focus on feed and sidestreams - Smárason, Birgir Örn; Samúelsdóttir, Anna Berg; Þórðarson, Gunnar; Geirsdóttir, Margrét (Zenodo, 2024)
Norðurlöndin eru stórir aðilar í fiskeldi m.a. á laxi ( Salmo salar ). Mörg krefjandi umhverfismál tengjast þessari framleiðslu og þau eru að finna í hverju skrefi ferlisins. Megináherslan í þessari skýrslu hefur verið lögð á ný fóðurhráefni og bætta nýtingu hliðarafurða. Bæði þessi mál snúa að miklu magni og það skiptir miklu máli fyrir atvinnulífið sem og sjálfbærni og umhverfisáhrif þessarar mikilvægu starfsgreina að þau séu tekin á betri og skilvirkari hátt en núverandi aðferðir. Framtíðarmatvælaöryggi fyrir matvæli fyrir jarðarbúa okkar, á sjálfbæran hátt til lengri tíma litið, krefst byltingar í því hvernig við framleiðum matinn okkar. Brýn þörf er á að hámarka sjálfbæra fóðurframleiðslu. _____ The Nordic countries are big players in salmon aquaculture ( Salmo salar ). Many challenging environmental issues are related to this production, and they are to be found in every step of the process. The main focus in this report has been put on novel and alternative feed ingredients and sidestreams utilisation. Both those issues involve vast volumes and it´s of high importance for the economy as well as the sustainability and environmental impact of this important profession that they are tackled in better and more efficient manner than current approaches. Future food security for our global population that does not compromise the long-term sustainability of our ecosystems requires a revolution in the way we produce our food and there is an urgent need for nutritionally optimise a sustainably produced feed ingredient for inclusion in aquafeeds.